Complete pleats : pleating techniques for fashion, architecture and design - Jackson, Paul (London : Laurence King Publishing, 2015)
Suitable for anyone wishing to create and make pleats, this book explains how pleating systems can be stretched, compressed, flared, skewed, multiplied and mirrored, showing how from simple ideas, a huge number of original pleat forms can be created.
boek